PENGARUH PUPUK KANDANGAN TERHADAP SERAPAN Cr PADA KACANG TANAH - Sudaryono Sudaryono (Jurnal Teknologi Lingkungan, 2007)
Naturally, the farm damage cure effect of heavy metal waste dismissalwill need very long time, but with growing of knowledge and technologyhence the damage cure acceleratable by passing input bacterium orbioremidiasi into impure land.Organic materials in compost or cage manure have role of vitalimportance in influencing heavy metal availability in land. Organic Manureusage can degrade heavy metal content of chromium at impure landuntil 67 - 68 %. The degradation of heavy metal content in land havecorrelation to level of chromium content to quality of agro product andcrop. Standard gyration quality for chromium content range from 0,5 -1,0 ppm, while chromium content in peanut crop > 0,5 ppm, so that isnot peaceful if exploited for livestock food, but chromium content atseed reside in below standard quality of competent so that to beconsumed, however for certainty have to be seen other heavy metalcontent (cadmium).